Influence of Iron, Cobalt, and Vitamin B12 Supply on Phytoplankton Growth in the Tropical East Pacific During the 2015 El Niño. Issue 12 (21st June 2018) - Browning, Thomas J.; Rapp, Insa; Schlosser, Christian; Gledhill, Martha; Achterberg, Eric P.; Bracher, Astrid; Le Moigne, Frédéric A. C.
Abstract: Iron (Fe), cobalt (Co), and vitamin B12 addition experiments were performed in the eastern Equatorial Pacific/Peruvian upwelling zone during the 2015 El Niño event. Near the Peruvian coastline, apparent photosystem II photochemical efficiencies ( F v / F m ) were unchanged by nutrient addition and chlorophyll a tripled in untreated controls over 2 days, indicating nutrient replete conditions. Conversely, Fe amendment further away from the coastline in the high nitrate, low Fe zone significantly increased F v / F m and chlorophyll a concentrations. Mean chlorophyll a was further enhanced following supply of Fe + Co and Fe + B12 relative to Fe alone, but this was not statistically significant; further offshore, reported Co depletion relative to Fe could enhance responses. The persistence of Fe limitation in this system under a developing El Niño, as previously demonstrated under non‐El Niño conditions, suggests that diminished upwelled Fe is likely an important factor driving reductions in offshore phytoplankton productivity during these events. Plain Language Summary: Phytoplankton productivity in the Equatorial Pacific is critical for curbing CO2 outgassing from upwelling waters and sustaining globally important fisheries. We tested which micronutrients were limiting phytoplankton growth in the Equatorial Pacific during the 2015 El Niño. To date evidence for nutrient limitation status during these events remains indirect. We show iron is limiting offshore of Peru and that cobalt or vitamin B12 could be approaching limitation, with limitation by the latter micronutrients possibly becoming more important further offshore. Linked to satellite data, the new results shed light on critical controls on marine productivity in this biogeochemically/economically important region. Our results suggest reduced upwelled iron‐predicted under El Niño conditions would be primarily responsible for observed offshore Peru productivity decreases. Key Points: Iron, cobalt, and vitamin B12 amendments were performed in the Equatorial Pacific/Peru upwelling zone at the onset of the 2015 El Niño The El Niño Peru upwelling had residual nitrate and exhibited recovery from community‐level iron stress following iron amendment Mean chlorophyll was enhanced in response to combined iron and cobalt/B12 amendment over iron only but was not statistically significant